2018
DOI: 10.22219/jtiumm.vol19.no2.118-126
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kepemimpinan Transformasional Dan Budaya Organisasi Terhadap Kepuasan Kerja Serta Dampaknya Pada Kinerja Karyawan

Abstract: This study aims to analyze employee performance. Employee performance is the result of thinking and energy from an employee to the existing job, can be tangible, seen, employee performance by some factors that are Transformational Leadership, Organizational Culture, and Job Satisfaction. Referring to the purpose of research that is done is to analyze and analyze various variables, then this research is descriptive and verificative. In descriptive analysis explained the dependent variables on which the theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 3 publications
4
12
2
4
Order By: Relevance
“…On the other hand, maintaining a transparent organizational culture can support teachers in carrying out their profession following the values and norms of society [44]. The findings of this research are in agreement with the research results [45]; [46]; [47], whose findings report that there is a significant effect of organizational culture on teacher performance. The practice of a pleasant organizational culture encourages teachers to carry out their duties competently and the impact will be seen from the results of the activities they have undertaken [48].…”
Section: The Influence Of Organizational Culture On Teacher Performancesupporting
confidence: 90%
“…On the other hand, maintaining a transparent organizational culture can support teachers in carrying out their profession following the values and norms of society [44]. The findings of this research are in agreement with the research results [45]; [46]; [47], whose findings report that there is a significant effect of organizational culture on teacher performance. The practice of a pleasant organizational culture encourages teachers to carry out their duties competently and the impact will be seen from the results of the activities they have undertaken [48].…”
Section: The Influence Of Organizational Culture On Teacher Performancesupporting
confidence: 90%
“…Based on the test results, it shows that organizational culture partially has a positive and significant effect on job satisfaction at CV Saudara Mulya Bersama. These results are in accordance with research conducted by Wahyuniardi et al (2018) with the title of research on the influence of organizational culture and work environment on job satisfaction and employee performance. With the results showing that organizational culture has a direct and positive influence on job satisfaction.…”
Section: T Testsupporting
confidence: 91%
“…If the organization is equated with humans, then the organizational culture is the personality of the organization. In a research conducted by Wahyuniardi & Nababan (2018) stated that a good organizational culture can have an impact on satisfaction with what employees have done, this statement is proven by the results of their research that organizational culture has a direct and positive influence on job satisfaction at PLN. West Java distribution, Majalaya area Based on the theory and previous research that has been obtained and put forward regarding job satisfaction, work environment, and organizational culture, the researcher describes a research model as follows:…”
Section: Literature Reviewmentioning
confidence: 93%
See 1 more Smart Citation
“…Aqmarina et a (2016)] conducted research and concluded that the type of transformational leadership negatively and not significantly influence employee performance transactional leadership while no significant influence on employee performance. Wahyuniardi et al (2018) conducted research and concluded that the type of transformational leadership has a significant effect on job satisfaction, the kind of transformational leadership has no significant influence on employee performance, organizational culture has no significant impact on employee performance, and job satisfaction did not significantly affect the performance of the employee. To improve employee performance can be done by increasing job satisfaction if job satisfaction increases, the performance of employees will also increase.…”
Section: Introductionmentioning
confidence: 99%